Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2015
DOI: 10.1002/adma.201405116
|View full text |Cite
|
Sign up to set email alerts
|

High‐Gain and Low‐Driving‐Voltage Photodetectors Based on Organolead Triiodide Perovskites

Abstract: In this paper, we describe the fabrication and characterization of solution-processed CH 3 NH 3 PbI 3 photodetectors that combine a high photoconductive gain with a broad spectral response, ranging from the UV to the NIR. Benefi tting from the trapped-hole-induced electron injection, the CH 3 NH 3 PbI 3 photodetector works as a photodiode in the dark and shows large photoconductive gain under illumination. The maximum device gain reached 489 ± 6 at a very low driving voltage of −1 V.The devices studied here ha… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

13
494
0
2

Year Published

2015
2015
2022
2022

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 599 publications
(509 citation statements)
references
References 33 publications
13
494
0
2
Order By: Relevance
“…72 This yielded photoconductive gains up to 400 with a response speed on the order of µs and 85 dB of linearity (Fig. 2e).…”
Section: Metal Halide Perovskite Photodetectorsmentioning
confidence: 99%
See 1 more Smart Citation
“…72 This yielded photoconductive gains up to 400 with a response speed on the order of µs and 85 dB of linearity (Fig. 2e).…”
Section: Metal Halide Perovskite Photodetectorsmentioning
confidence: 99%
“…2e). 72 Also similar to organic semiconductors, MHPs can be combined with inorganic nanoparticles. Liu et al have recently reported on the use of PbS QDs in order to expand the spectral bandwidth of MHPs to the NIR.…”
Section: Metal Halide Perovskite Photodetectorsmentioning
confidence: 99%
“…The commonly employed electrodes include gold (Au), silver (Ag), copper (Cu), platinum (Pt), titanium (Ti), aluminum (Al), graphene, and indium tin oxide (ITO) 35, 78, 79, 80, 81, 82. Different metals with varying Fermi levels will form Ohmic or Schottky contacts with OIHPs due to energy alignment, resulting in symmetrical and linear or asymmetrical and nonlinear I – V characteristics 82.…”
Section: Factors Influencing Photodetectors Performancesmentioning
confidence: 99%
“…Several studies have clarified the rare ability of CH 3 NH 3 PbI 3 as photodetector to achieve high gain of photoinduced current in which quantum yield of photon-toelectron (current) far exceeds 100%. 38,75,76 For a semiconductor device to work as the photodetector, device is reverse-biased by external voltage so that the photocurrent density is maximized while the dark current is minimized. Here, ratio of photo-and dark-currents corresponds to the S/N ratio in photon detection.…”
Section: Optoelectronic Functions As Photodetectormentioning
confidence: 99%